The Long-run Impact of the Massachusetts Education Reform Act (MERA) on Educational Equality in Massachusetts with Proposition 2 ½ Overrides - Kim, Jaeho. (2018)
Abstract: As part of the Massachusetts Education Reform Act (MERA) of 1993, which has been the most significant change in Massachusetts K-12 education in the last 25 years, Chapter 70 was created. Chapter 70 has both adequacy and equity measures and the main question of this paper is whether these two characteristics of MERA contribute to improving educational equality in Massachusetts. A Difference-in-differences (DID) estimation based on an event study method shows that MERA has decreased the achievement and spending gap and income segregation between the poor and rich districts. Passing a Proposition 2 ½ override vote enhances the impact of MERA on equalizing education spending, but contradicts the role of MERA in reducing income segregation.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Thomas Downes, and David Garman.; Keyword: Economics.